Method for separating boron isotope by using ferroferric oxide / resin microspheres

By using ferrotetraoxide/resin microspheres and adsorption and desorption solution at specific pH, the problem of low boron isotope separation efficiency in the prior art is solved, and efficient 10B enrichment and long-life column performance is achieved.

CN119565374APending Publication Date: 2025-03-07SHANDONG CHENGWU YIXIN ENVIRONMENTAL TECH CO LTD

Patent Information

Application Number
CN202411855387.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the prior art, the adsorption and separation efficiency of 10B and 11B isotopes in aqueous boric acid solution is low, and the service life of the separation material is not easily guaranteed.

Method used

Iron tetraoxide/resin microspheres are used as the stationary phase, and boric acid-boronic acid monosodium solution with pH 6-7 as the adsorption solution and sodium hydroxide aqueous solution with pH 10-11 as the desorption solution to achieve efficient separation of boron isotopes.

Benefits of technology

The high enrichment of 10B in the aqueous boric acid solution was achieved, the separation factor reached 1.312, the service life of the chromatographic column was relatively long, and the overall performance was better than that of the existing technology.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a method for separating boron isotopes by using ferroferric oxide / resin microspheres, which comprises the following steps: in a chromatographic column, taking a boric acid-monosodium borate aqueous solution with the pH value of 6-7 as an adsorption solution, and taking a sodium hydroxide aqueous solution with the pH value of 10-11 as a desorption solution to obtain a 10B-rich boric acid aqueous solution; the preparation method of the microspheres comprises the following steps: (1) adding dimethyl sulfoxide to swell polystyrene-divinylbenzene resin microspheres, adding concentrated sulfuric acid to treat until the sulfonation rate is 0.3-0.4 mmol / g, washing with water, treating with an ammonium chloride aqueous solution, washing with water, drying in vacuum, spraying with a ferric chloride-ferrous chloride aqueous solution, evaporating in vacuum to remove part of water, and introducing ammonia-containing nitrogen flow to treat to obtain polystyrene-divinylbenzene resin microspheres; and washing with water, grinding the surface, treating with a sodium hydroxide aqueous solution and washing with water. The method is simple in separation operation, easy to implement and high in efficiency, and has a certain application prospect; the chromatographic column is relatively stable in performance, reproducible and relatively long in service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of boron isotope separation, and in particular relates to a method for separating boron isotopes by utilizing ferroferric oxide / resin microspheres. Background Art

[0002] 10 B and 11 B is the two stable isotopes of boron, with natural abundances of 19.9% ​​and 80.1% respectively. 10 The thermal neutron capture cross section of B is much larger than 11 B, used in the nuclear industry for reactor control rod materials (such as boron carbide), pressurized water reactor coolants (such as boric acid aqueous solution) and neutron shielding materials (such as boron-containing polyethylene), and in medicine as a targeting agent for the treatment of certain tumors (boron neutron capture therapy); in these applications, 10 The abundance of B has certain requirements, except for some neutron shielding materials, it is above 85%. 10 The main methods of B are: BF3 low temperature distillation, chemical exchange distillation and chromatography; among them, chromatography has the characteristics of energy saving and safety. 10 B and 11 B, is a separation method with great development potential

[0003] In the prior art, ion exchange or adsorption resins, such as strongly acidic cation exchange resins, strongly basic anion exchange resins, weakly basic anion exchange resins, and boron-specific adsorption resins AMBERLITE IRA743 and weakly acidic cation exchange resins, are used to adsorb boric acid in aqueous solution. 10 B and 11 The adsorption and separation efficiency of B isotopes are poor and have no practical value ( 10 B / 11 B separation coefficient, i.e., separation factor, is lower than 1.1). Therefore, it is necessary to develop a new boron adsorption separation material for boron isotope separation in boric acid aqueous solution.

[0004] CN109464981A provides a method for preparing a magnetic nanomaterial and a method for separating boron isotopes using the magnetic nanomaterial, and discloses methods for preparing four magnetic nanomaterials: Fe3O4, SiO2@Fe3O4, Carbon@Fe3O4, and Fe3O4@CuO. For example, a method for preparing a magnetic nanomaterial Fe3O4 comprises the following steps: (1) weighing 8.1 g of FeCl3·6H2O and 3.9 g of FeCl2·4H2O, placing them in a round-bottom flask, adding 540 mL of deionized water and a magnet, fixing the round-bottom flask on a magnetic stirrer, and connecting a balloon filled with nitrogen to dissolve the substances under magnetic stirring; (2) after the two substances are completely dissolved, under strong magnetic stirring and nitrogen protection, adding 60 mL of ammonia water to adjust the pH to about 8, at which point the solution changes from red to black, and the reaction time is 1 hour; (3) after the reaction is completed, separating the product with a magnet and washing it, and adjusting the pH of the solution to neutral with hydrochloric acid during the last washing; (4) drying the product under vacuum at 40°C for 8 hours. In the embodiment, 0.10 g of the prepared metal oxide nanomaterials were weighed and added to a 0.5 mol / L boric acid aqueous solution, shaken at 140 rpm for 6 hours, filtered, centrifuged, and the boric acid concentration and isotope abundance in the aqueous solution after treatment were detected to calculate the boron isotope. 10 B / 11 B separation factor; the four materials all showed a relatively high boron isotope separation factor of 1.118-1.332, among which Fe3O4 had the best overall effect. The relevant doctoral dissertation "Application and Mechanism Study of Boron Adsorption and Boron Isotope Separation by Magnetic Nanoparticles (Fe3O4)" (Chen Tao, Tianjin University, May 2022) disclosed the adsorption, desorption and isotope separation efficiency of Fe3O4 nanoparticles (prepared by co-precipitation method) for boron in aqueous boric acid solutions of different concentrations, pH values ​​and temperatures, as well as the performance attenuation of the material. The nanomaterials prepared by the prior art are ultrafine powders, which are difficult to use as chromatographic column stationary phases. The nanopowders are pressure-formed, crushed, and sieved to obtain granules with a particle size of 0.2-1 mm. When used in chromatographic columns, they have low wear resistance (easy to fall off) and a contradiction between strength and internal pore volume. When the strength is guaranteed, the internal pores are significantly compressed, and the adsorption and separation ability of the granules for boric acid is greatly reduced.

[0005] In the master's thesis "Preparation of Fe3O4-loaded Resin and Study on Boron Isotope Separation Performance" (Wang Qingfeng, Tianjin University, May 2021), a microsphere material (Fe3O4@Resin) prepared by pre-exchange-coprecipitation method and loaded with Fe3O4 nanoparticles (loading amount of about 8.1wt%) by macroporous strongly acidic cation exchange resin (D001 resin microsphere) was disclosed, and its physical and chemical properties and chromatographic separation of boron isotopes were studied; the indicators of the D001 resin used were: styrene-divinylbenzene system, the functional group was -SO3 - , mass total exchange capacity (dry) ≥ 4mmol / g, volume total exchange capacity (wet) ≥ 1mmol / mL, particle size 0.315-1.25mm, water content 42-55%. Among them, Fe3O4@Resin-1 has a better effect. The preparation method is as follows: 40mL D001 resin converted to hydrogen form after pretreatment, 8.1g FeCl3·6H2O and 540mL deionized water are added to a round-bottom flask, and stirred for 12h under N2 conditions to make D001 resin and Fe 3+ Perform sufficient ion exchange; then add 3.9g FeCl2·4H2O and wait until it is completely dissolved in the mixture (Fe 3+ with Fe 2+ The reaction was completed after 1 hour, and Fe3O4@Resin-1 particles (the iron oxide content was 8.1 wt % based on the dry basis of Fe3O4@Resin-1 and Fe3O4) were obtained by static precipitation. The particles were washed 3 times with ethanol and deionized water respectively, dried in vacuum at 40°C for 10 hours, and sieved with 24-mesh and 32-mesh sieves to obtain particles with a particle size of 0.56-0.8 mm, which were then used in subsequent experiments. Fe3O4 nanoparticles (without resin) were also synthesized by coprecipitation method as a control: 8.1gFeCl3·6H2O, 3.9gFeCl2·4H2O and 540mL deionized water were added to a round-bottom flask, stirred under N2 conditions, and 60mL ammonia water was added to cause coprecipitation reaction after all dissolved. The remaining operation steps and conditions were consistent with those of Fe3O4@Resin-1, and finally a microsphere material loaded with Fe3O4 nanoparticles was obtained. The XRD method detected that the grain size of the Fe3O4 nanoparticles on the surface of Fe3O4@Resin-1 was 13nm, and the grain size of the pure Fe3O4 nanoparticles (without resin) in the control was also 13nm; the SEM method detected that the surface of the Fe3O4@Resin particles was coated with a layer of Fe3O4 nanoparticles, and it was relatively rough. The zero charge point (pHzpc) of Fe3O4@Resin-1 is 6.75. The boron adsorption and separation factor are both large when the pH of the boric acid aqueous solution is 6-7. The maximum boron adsorption is 2.869 mg·g at pH 7.-1 , at pH 6, about 2.65 mg g -1 , which significantly decreased at other pH values; the separation factor was 1.315 at pH 6 and about 1.305 at pH 7, which decreased at other pH values; the adsorption kinetics data were consistent with the pseudo-second-order kinetic model; the adsorption isotherm data were consistent with the Langmuir model. The activated Fe3O4@Resin-1 material (58.81 g) was wet-filled into a stainless steel column with a length of 25 cm and an inner diameter of 2.2 cm, and boron isotope chromatographic separation (dynamic separation) was performed: the boron concentration was 5.405 g·L -1 , 10 B abundance 19.78% ( 11 The boric acid aqueous solution (B abundance 80.22%) was adjusted to pH 7 with sodium hydroxide aqueous solution and the flow rate was 5 mL min -1 , the column temperature was 25℃, and the liquid was continuously injected for 60 min; then the concentration of 0.01 mol·L -1 The hydrochloric acid solution was used as the eluent at a flow rate of 5 mL min -1 , the column temperature was 25℃, and the liquid was continuously added for 1.5h to elute the boric acid adsorbed on the Fe3O4@Resin-1 filler; finally, deionized water was continuously added until the effluent was neutral, and the hydrochloric acid solution in the chromatographic column was completely replaced by water to complete the regeneration; the adsorption-regeneration process was repeated five times. As a result, the separation factor reached 1.312, the column pressure drop was below 2MPa, and the elution was 10 The boric acid aqueous solution with a boric acid abundance of 22.76% was used; however, the boron adsorption separation performance gradually decreased with each adsorption-regeneration process. 10 The adsorption amounts of B were 0.03275g, 0.03218g, 0.03172g, 0.03131g, and 0.03088g, respectively, and the recovery rates were 95.98%, 94.31%, 92.97%, 91.76%, and 90.50%, respectively. In the prior art, the Fe3O4 nanoparticles loaded by the microsphere material are basically coated on the surface of the resin microspheres. Under the extrusion force of the chromatographic column bed, the Fe3O4 nanoparticle coating is easily worn and fallen off; Fe 3+ with Fe 2+ The molar ratio of the feed is 3:2, and the 3+ with Fe 2+ The molar ratio of the feed required to generate Fe3O4 by neutralization precipitation reaction is different from 2:1, which indicates that part of Fe is needed in the preparation process. 2+ The oxidation of the prepared microspheres may cause changes in the adsorption and separation performance of the prepared microspheres during use due to changes in the valence of Fe, or the ion exchange resin (D001) is still in the trivalent iron type, that is, Fe combined with sulfonic acid groups. 3+ Not all of it is converted into Fe3O4.

[0006] In the above-mentioned prior art, the elution process after the separation material adsorbs boric acid requires two liquid flows, such as a dilute acid aqueous solution with a pH value of 2-6 and water. If used for chromatographic separation, the operation is relatively cumbersome, and the corrosive effect of the dilute acid (such as when the pH value is 2-4) will also make it difficult to guarantee the life of the adsorption separation material; therefore, the above-mentioned adsorption separation materials are difficult to use.

[0007] Therefore, it is necessary to prepare microspherical materials with better overall performance and capable of being loaded into chromatographic columns for boron isotope separation, so that the boric acid in aqueous solution can be separated by conventional and simple chromatographic separation methods. 10 B is enriched to a higher degree and the column has a longer service life. Summary of the invention

[0008] In order to solve the above technical problems, the present invention provides a method for separating boron isotopes using ferroferric oxide / resin microspheres, using a chromatographic column with ferroferric oxide / resin microspheres as the stationary phase, a boric acid-monosodium borate aqueous solution with a pH value of 6-7 as the adsorption liquid, and a sodium hydroxide aqueous solution with a pH value of 10-11 as the desorption liquid to obtain a boron isotope-rich 10 B. Boric acid aqueous solution;

[0009] The ferroferric oxide / resin microspheres are prepared by the following steps:

[0010] (1) Cross-linking degree 15-30, specific surface area 100-180m 2 / g, pore volume 0.6-1.0mL / g, dried (120℃x3h baking loss ≤0.2wt%) polystyrene-divinylbenzene resin microspheres, adding dimethyl sulfoxide in air-tight and anhydrous conditions, heating to 50-65℃ for swelling for more than 3h, adding 93-98wt% concentrated sulfuric acid for sulfonation treatment during stirring, controlling the temperature to 55-65℃, and performing solid-liquid separation after the sulfonation rate reaches 0.3-0.4mmol / g, washing the microspheres with water until the pH value is ≥2, adding 2-5mol / L ammonia solution for immersion for 2-5h for primary ion exchange transformation from hydrogen type to ammonium type, washing with water to obtain water-containing ammonium type macroporous polystyrene-divinylbenzene ion exchange resin microspheres;

[0011] During the sulfonation treatment, the weight ratio of polystyrene-divinylbenzene microspheres, dimethyl sulfoxide, and concentrated sulfuric acid is 1:(4-5):(0.3-0.5);

[0012] (2) The ammonium macroporous polystyrene-divinylbenzene ion exchange resin microspheres containing water in step (1) are transferred to a rotary drum that can be evacuated, equipped with external heating and an atomizing nozzle, sealed and started to rotate, and vacuum dried at 60-70° C. until the water content is less than 1wt% to obtain dried ammonium macroporous polystyrene-divinylbenzene ion exchange resin microspheres; further evacuated and cooled to 50-60° C., filled with high-purity nitrogen to positive pressure, and atomized sprayed with a ferric chloride-ferrous chloride aqueous solution with a concentration of 2-3 mol / L and a temperature of 50-60° C. for 4-6 hours, and the rotary drum is continuously rotated for 0.5-1 hour until the resin microspheres are After all the solution on the ball surface is absorbed, the rotation is stopped, and the ball is allowed to stand for 3-5 hours for homogenization (homogenization of the ferric chloride-ferrous chloride aqueous solution initially absorbed in the resin microspheres) and secondary ion exchange transformation from ammonium type to iron type, and the temperature of the microsphere material is maintained at 50-60° C. and the positive pressure in the drum is maintained during the spraying and homogenization and secondary ion exchange transformation process; the spraying volume of the ferric chloride-ferrous chloride aqueous solution is 70-85% of the saturated water absorption volume of the dried ammonium type resin microspheres; in the ferric chloride-ferrous chloride aqueous solution, the molar ratio of ferric chloride to ferrous chloride is 2:1;

[0013] The drum is started, and the external heating temperature is controlled to be 60-70° C. and the required vacuum conditions are controlled. Within 8-12 hours, 25-40% of the total weight of the water contained in the microsphere material is uniformly evaporated and removed, and high-purity nitrogen is filled to positive pressure, and the temperature of the microsphere material is reduced to 50-60° C.; the drum continues to rotate, and a nitrogen gas flow with a temperature of 50-60° C., a relative humidity of 35-45%, and an ammonia content of 0.5-1v% is introduced at a required fixed flow rate to treat the microsphere material, so that no ammonia is consumed during ventilation for 4-8 hours (that is, the ammonia content in the outlet and inlet gas flows is the same), and the ammonia-containing nitrogen gas flow is continued for 0.5-1 hour to perform a tertiary ion exchange transformation from trivalent iron type to ammonium type; during the treatment with the ammonia-containing nitrogen gas flow, the temperature of the microsphere material is maintained at 50-60° C. and the positive pressure in the drum is maintained;

[0014] The drum continues to rotate and high-purity nitrogen is passed to maintain the positive pressure in the drum. Deoxygenated water at 40-50°C is sprayed on the microsphere material. The amount of water sprayed is 2-3 times the accumulated volume of the microsphere material. The drum is rotated for 30-60 minutes to wash the microsphere material once. The drum is stopped to discharge the liquid between the microspheres. The washing and drainage process is repeated 2-3 times. The drum is stopped to discharge the liquid between the microspheres. The drum is started to spray the microsphere material with a concentration of 0.8-1 mol / L and a temperature of 30-40°C. The sodium hydroxide aqueous solution is sprayed in an amount of 1-1.5 times the accumulated volume of the microsphere material, the drum is stopped, and the mixture is allowed to stand for 2-3 hours for a fourth ion exchange transformation from ammonium type to sodium type, and then the liquid between the microspheres is discharged; deoxygenated water at room temperature is used instead, and the water washing and draining process is repeated 3-5 times, and then the microsphere material is sprayed with deoxygenated water at room temperature until the microsphere material is immersed, and the microsphere and the immersion water are discharged into a container pre-substituted with nitrogen and the container is sealed to obtain ferroferric oxide / resin microspheres.

[0015] The present invention utilizes ferroferric oxide / resin microspheres to separate boric acid aqueous solution 10 B. 11 The method for separating B boron isotopes, and the preferred separation operating conditions include: the chromatographic column is installed vertically, the height-to-diameter ratio is 10-60, the column temperature is 15-35°C, the adsorption liquid (boric acid-monosodium borate aqueous solution) and the desorption liquid (sodium hydroxide aqueous solution) are both in the top and out the bottom; the boric acid concentration in the boric acid-monosodium borate aqueous solution is 80-95% of the saturated concentration in water under the column temperature conditions; the apparent or axial flow rate of the adsorption liquid and the desorption liquid in the stationary phase bed is 0.4-0.6m / h. The preferred equipment conditions include: the chromatographic column adopts a cylindrical barrel, a separation bed filled with the stationary phase, i.e., the ferroferric oxide / resin microspheres, is arranged in the barrel, a screen, porcelain balls, metal orifice plates and other heavy pressure materials are arranged on the separation bed to compress the separation bed and disperse the liquid flow, a screen and a support are arranged under the separation bed, and an insulation layer or a circulating water jacket is arranged outside the barrel; an electric valve is appropriately arranged in the inlet and outlet interfaces of the chromatographic column or its connecting pipeline, as well as measurement / control components of a temperature measuring instrument, a concentration meter and a flow meter; the electric valve and the instrument are connected to an intelligent controller, the intelligent controller is connected to a computer, and the control of the inlet and outlet, the solution segmentation logic and the flow control are realized through the computer settings, so as to control the inlet selection, the outlet direction and the segmentation and collection of the outlet. The measurement components of the concentration meter include a boric acid concentration transmitter and a pH value transmitter.

[0016] The adsorption liquid, i.e., a boric acid-monosodium borate aqueous solution with a pH value of 6-7, can be prepared from water, boric acid, sodium hydroxide or a sodium hydroxide aqueous solution with a concentration of 0.5-3 mol / L; the volume of the adsorption liquid once fed is 12-15% of the volume of the separation bed. After a period of operation, if the separation efficiency of the chromatographic column is reduced, it can be regenerated with a 0.3-0.5 mol / L sodium hydroxide aqueous solution, and after regeneration, the influent water is rinsed until the conductivity of the discharged water is less than 10 μs / cm, so that the performance of the chromatographic column can be restored to a large extent; the discharged liquid in the regeneration process contains sodium hydroxide and monosodium borate, which can be used to prepare the boric acid-monosodium borate aqueous solution with a pH value of 6-7, i.e., the adsorption liquid.

[0017] The boric acid and sodium hydroxide (or concentrated sodium hydroxide solution) used in the preparation of the adsorption liquid and the desorption liquid should have appropriately high purity, and the impurity content other than water should preferably be less than 0.1wt%, and more preferably less than 0.03wt%; the water used to prepare the boric acid-monosodium borate aqueous solution and the pure water used as the desorption liquid should not contain organic components and O2, and the electrical conductivity should be less than 0.2μs / cm. It is preferably high-purity distilled water obtained by further distilling deionized water or reverse osmosis water after slightly boiling to remove impurities such as O2 and CO2.

[0018] The effluent from the chromatographic column is divided and collected to obtain a certain concentration and 10 B. 11 The aqueous solution containing boric acid with a concentration of B can be initially concentrated by reverse osmosis and then further processed and utilized; most of the desorption liquid is recycled, and after the pH value drops, a relatively concentrated aqueous solution of sodium hydroxide is added to adjust it back to 10-11; after the remaining liquid flow is collected, it can be concentrated by reverse osmosis and then used as a component of the adsorption liquid.

[0019] In the preparation step (1) of ferroferric oxide / resin microspheres, the polystyrene-divinylbenzene microspheres are white balls obtained by removing the porogen from the mixed ingredients containing the porogen after forming the spheres by suspension polymerization, washing with water (using hot water and cold water in sequence), and drying, with an outer diameter of 0.3-1.3 mm; the pore volume is a calculated result obtained from the measurement results of the apparent density and the skeleton density. The specific surface area is measured by low-temperature nitrogen adsorption method, and the pore volume and pore diameter are measured by scanning porosimetry.

[0020] In step (2), the atomizing nozzle adopts hydraulic atomization when spraying liquid and water, and high-purity nitrogen and ammonia-containing nitrogen gas flow are also introduced into the nozzle; the O2 content in the high-purity nitrogen is preferably less than 30ppmv, that is, less than one ten-thousandth of the volume, to avoid oxidation of ferrous chloride; the positive pressure maintained by nitrogen filling the drum can be 15-30kPa to control the infiltration of O2 in the air; during the vacuum drying of the ammonium microsphere material, the air in the microsphere gap and the drum is basically removed as the steam is extracted; the nitrogen gas flow with a temperature of 50-60°C, a relative humidity of 35-45%, and ammonia content of 0.5-1v% is preferably less than 30ppmv, and its relative humidity is controlled by a condensation method or a desiccant method The system preferably uses a recycled ammonia-nitrogen gas flow to reduce nitrogen consumption; the uniform evaporation and removal process of 25-40% of the total weight of water contained in the microsphere material (loaded with ferric chloride-ferrous chloride aqueous solution) under 60-70°C and vacuum conditions can be achieved by adjusting the vacuum degree by fixing the external heating temperature, and controlling the condensation amount of the exhaust steam to be basically uniform; the deoxygenated water is pure water obtained by removing impurities such as O2 and CO2 from deionized pure water or reverse osmosis pure water through micro-boiling, and the sodium hydroxide aqueous solution is prepared with deoxygenated water; the washing end point of ferroferric oxide / resin microspheres can be determined according to the conductivity of the exhaust water, and the conductivity of the exhaust water can be less than 10μs / cm, preferably less than 5μs / cm. The unit v% is the volume percentage; the unit ppmv is one millionth of the volume.

[0021] In step (2), the ferric chloride-ferrous chloride aqueous solution may also contain 0.01-0.03 mol / L titanium trichloride, which is found to improve the boric acid adsorption capacity of the prepared ferroferric oxide / resin microspheres. 10 B. 11 B Separation efficiency, especially the stability of separation performance.

[0022] The present invention utilizes ferroferric oxide / resin microspheres to separate boric acid aqueous solution, 11 The beneficial effects of the method for isotope B boron include: the chromatographic separation operation is simple, easy and efficient, and the boric acid aqueous solution can be separated into 10 B was enriched to a higher degree by 10 B Boric acid aqueous solution is iteratively separated to obtain 10 Aqueous solution containing boric acid with a boric acid abundance of more than 90%; The chromatographic column has a relatively stable boric acid adsorption capacity and 10 B. 11 B separation performance, long service life, overall performance is better than the existing chromatography separation technology, and has certain application prospects.

[0023] From the effects of the following embodiments and comparative examples, it is believed that the main principles of the present invention are as follows, and the above beneficial effects are also the result of the following factors:

[0024] 1. In the method of the present invention, under the chromatographic separation conditions, the ferroferric oxide / resin microspheres can maintain a high 10 B. 11 B separation efficiency, indicating that the ferroferric oxide nanoparticles loaded in the pores of the resin microspheres have an effect on the adsorption of the boric acid-sodium borate aqueous solution at pH 6-7. 10 Component B has good affinity, and the desorption efficiency of sodium hydroxide aqueous solution with pH value of 10-11 is higher; the corrosion of the loaded ferroferric oxide nanoparticles by the desorption solution is also much lighter than that of the prior art using dilute hydrochloric acid aqueous solution with pH value of 3.5-4.5 as the desorption solution. In the adsorption solution with pH value of 6-7, the concentration of boric acid is 0.5-1 mol / L (depending on the solution temperature and column temperature), and the concentration of monosodium borate is generally 0.01-0.05 mol / L (which can be achieved by adding 0.01-0.05 mol / L of sodium hydroxide); in the desorption solution with pH value of 10-11, the concentration of sodium hydroxide is 10 -4 -10 - 3 mol / L. When the desorption liquid contacts the adsorption liquid, the low concentration of sodium hydroxide contained in it is immediately neutralized by boric acid to generate monosodium borate. Therefore, the separation bed has a horizontal and layered transition zone with a pH value of 7-10 along its axis, which gradually moves downward. The desorption effect is slightly better than that of pure water. However, the desorbed ferric oxide / resin microspheres may have a negative impact on the content of 10 The adsorption selectivity of component B is better.

[0025] 2. In the method of the present invention, the use of a sodium hydroxide aqueous solution with a pH value of 10-11 as the desorption liquid can achieve a higher desorption rate than using high-purity distilled water and / or a dilute hydrochloric acid aqueous solution with a pH value of 3.5-4.5 as the desorption liquid. 10 B. 11B separation efficiency, and the decline of separation efficiency is much slower; and after the chromatographic column has been running for a long time, the adsorption and separation efficiency can be regenerated with 0.3-0.5mol / L sodium hydroxide solution and its performance can be basically restored. The technical effects of these two aspects show that the surface of the ferric oxide nanoparticles loaded by the resin microspheres will gradually generate and deposit boric acid polymers, which are difficult to elute with water and dilute hydrochloric acid aqueous solution with a pH value of 3.5-4.5, resulting in a rapid decline in the adsorption and separation performance of the chromatographic column. However, when a sodium hydroxide aqueous solution with a pH value of 10-11 is used as a desorption liquid in the method of the present invention, the deposition rate of boric acid polymers on the surface of ferric oxide nanoparticles will be significantly reduced because it has a certain solubility for boric acid polymers; at the same time, the impurity content other than water in the boric acid and sodium hydroxide used is less than 0.1wt%, and the adsorption liquid and desorption liquid are prepared with high-purity distilled water, which reduces the contamination of the impurity components contained in the ferric oxide / resin microspheres. Under the combined effect of these factors, the long-term adsorption and separation performance and service life of the chromatographic column are guaranteed. When a sodium hydroxide aqueous solution with a pH value of 12 is used as the desorption liquid, the adsorption separation performance of the chromatographic column decreases. From the alkali washing regeneration effect in Examples 7 and 8, the number of separations before alkali washing regeneration, and the maximum concentration of monosodium borate in the effluent during the alkali washing process in terms of boric acid, it can be seen that in step (2) of the preparation process of ferrosoferric oxide / resin microspheres, adding 0.02 mol / L of titanium trichloride to the ferric chloride-ferrous chloride aqueous solution has a significant effect on improving the separation performance and stability of the chromatographic column.

[0026] 3. The monosodium borate has a molecular formula of NaB(OH)4, which can be ionized to [B(OH)4] - Boric acid is a Lewis acid. When combined with water in aqueous solution, it can ionize into trace amounts of [B(OH)4] - and H + When a 0.3-0.5 mol / L sodium hydroxide aqueous solution is used to regenerate the chromatographic column, the effluent contains monosodium borate generated by the reaction of residual boric acid with sodium hydroxide, and monosodium borate generated by the dissolution and depolymerization of boric acid polymers and the reaction with sodium hydroxide, which can be used to prepare the boric acid-monosodium borate aqueous solution (i.e., adsorption solution) at pH 6-7. The effluent can be considered to contain only sodium hydroxide and monosodium borate.

[0027] 4. In the preparation step (1) of the ferrosoferric oxide / resin microspheres, the polystyrene-divinylbenzene resin microspheres are added with dimethyl sulfoxide and swelled at 50-65°C for more than 3 hours. After being sulfonated with concentrated sulfuric acid until the sulfonation rate reaches 0.3-0.4 mmol / g, the microspheres have ion exchange capacity and good overall hydrophilicity. Concentrated sulfuric acid can be miscible with dimethyl sulfoxide, and sulfuric acid can quickly enter the inner pores of the resin microspheres, so that the sulfonation grafting reaction of the resin microspheres is more uniformly distributed among all the resin microspheres and in a single resin microsphere, and the sulfonation rate is easier to control to 0.3-0.4mmol / g; while in the conventional method of using conventional swelling agents such as dichloroethane to swell the resin and then perform sulfonation treatment, since the solubility of concentrated sulfuric acid in dichloroethane is very low and the two are easy to separate, the sulfonation rate is difficult to control to 0.3-0.4mmol / g, and the macroscopic distribution uniformity of the sulfonation grafting reaction between the resin microspheres and in a single resin microsphere is poor, which is not suitable for the present invention.

[0028] 5. In step (1), the sulfonation rate of the resin microspheres reaches 0.3-0.4mmol / g, that is, after the primary ion exchange transformation and water washing, the ammonium type macroporous polystyrene-divinylbenzene ion exchange resin microspheres obtained have a sulfonic acid group grafting amount much lower than the 4-5mmol / g of the conventional strongly acidic cation exchange resin, the purpose is to reduce the excessive occupation of the grafted sulfonic acid groups on the inner pore volume, so as to obtain a larger inner pore volume and specific surface area, improve the loading capacity and obtain better ferric oxide adsorption capacity and microsphere inner pore mass transfer capacity under the condition of equal ferric oxide loading amount. It is found that the size and number of ferric oxide grains can be affected and controlled to a certain extent. The reason should be that after the resin microspheres are converted to iron type by secondary ion exchange, the iron sulfonate on the inner pore surface plays the role of crystal seed; the lighter degree of sulfonation, that is, the hydrophilic modification of the polystyrene-divinylbenzene resin microspheres is achieved, which provides conditions for the subsequent immersion of ammonia solution and the spraying and inhalation of ferric chloride-ferrous chloride aqueous solution.

[0029] 6. In step (2), the ferric chloride-ferrous chloride aqueous solution sprayed by atomization has a high concentration and a certain viscosity. Even if all of it is absorbed into the resin microspheres, the distribution of ferric chloride and ferrous chloride components in the resin microspheres is still uneven. It is necessary to go through the 3-5h static homogenization process to achieve a basically uniform distribution in the resin microspheres. This is an important condition for the method of the present invention to load ferrous oxide nanoparticles more evenly in the pores of the resin microspheres. During the homogenization and secondary ion exchange transformation treatment process, the ferric chloride-ferrous chloride aqueous solution absorbed into the resin microspheres is evenly distributed in the pores, including the homogenization of the solution distribution and the homogenization of the chemical composition. The secondary transformation is an ion exchange transformation from ammonium type to trivalent iron type. In the ferric chloride-ferrous chloride aqueous solution, when containing 0.01-0.03mol / L of titanium trichloride, the boric acid adsorption capacity and 10 B. 11 B separation efficiency may be due to the fact that the hydrolysis product of titanium trichloride improves the surface properties of ferroferric oxide nanoparticles.

[0030] 7. In step (2), before the ammonia-nitrogen gas flow is introduced for treatment, 25-40% of the total weight of the water contained in the microspheres is removed by vacuum evaporation, so that the ferric chloride-ferrous chloride aqueous solution (containing more than 700g of water per liter of spraying liquid) in the inner pores is concentrated to form more ammonia mass transfer channels required for the ammonia-nitrogen gas flow treatment process in step (3), and the finally prepared ferrosoferric oxide / resin microspheres have better performance than when the vacuum evaporation for removing 25-40% of the total weight of the water contained in the microspheres is omitted. 10 B. 11 The main reason for the improved adsorption and separation performance of B boric acid is that the method of the present invention can obtain a relatively uniform distribution of ferroferric oxide nanoparticles in the inner pores of the resin microspheres. The ferroferric oxide / resin microspheres prepared by using the dried ammonium-type resin microspheres, spraying ferric chloride-ferrous chloride aqueous solution, vacuum evaporation to remove part of the water, treating with the ammonia-nitrogen gas flow, and generating ferroferric oxide nanoparticles in the inner pores also have better adsorption and separation performance than the hydrogen-type resin microspheres obtained by sulfonation and then washing in step (1), directly spraying ferric chloride-ferrous chloride aqueous solution, vacuum evaporation to remove part of the water, treating with the ammonia-nitrogen gas flow, and generating ferroferric oxide nanoparticles in the inner pores. 10 B. 11The main reason for the improved adsorption and separation performance of B boric acid may be that the method of the present invention can obtain a better distribution of ferroferric oxide nanoparticles in the inner pores of the resin microspheres, and the latter may be more easily distributed in the inner surface layer and the inner pore openings of the resin microspheres. During the treatment process at a temperature of 50-60°C, a relative humidity of 30-40%, and a nitrogen gas flow containing 0.5-1v% ammonia, the precipitation reaction of ferric chloride-ferrous chloride proceeds slowly, so that the generated ferroferric oxide nanoparticles are more evenly deposited in the inner pores of the resin microspheres, and are less concentrated on the surface layer and the pore openings of the microspheres. The microsphere material prepared under other precipitation conditions is 10 B. 11 B separation efficiency has deteriorated; among them, the relative humidity of 30-40% of the ammonia-nitrogen gas flow can ensure that the generation reaction of iron tetroxide nanoparticles is basically carried out in the liquid phase on the inner pore surface.

[0031] 8. In step (2), during the water washing process after the treatment with the ammonia-nitrogen gas flow, the drum drives the friction and flushing of the microsphere material, so that the surface of the microsphere is fully ground, and the small amount of ferroferric oxide nanoparticles deposited on the surface of the microsphere are basically ground and removed; thus, the prepared ferroferric oxide / resin microspheres have a good effect on the boric acid-monosodium borate aqueous solution. 10 B. 11 The adsorption and separation efficiency of B should be mainly due to the effect of the ferroferric oxide nanoparticles in the inner pores. The effect of treating the microsphere material with the sodium hydroxide aqueous solution with a concentration of 0.8-1 mol / L and a temperature of 30-40°C (the liquid volume is 1-1.5 times the accumulated volume of the microsphere material) is to convert the sulfonic acid group grafted on the surface of the microsphere inner pore from ammonium type (pH weakly acidic) to sodium type (pH neutral, i.e., four-time ion exchange transformation), which to a certain extent provides a pH neutral solution condition for the ferroferric oxide nanoparticles, thereby to a certain extent improving the prepared ferroferric oxide / resin microspheres to the boric acid-monosodium borate aqueous solution. 10 B. 11 B adsorption, separation efficiency; when not treated with the sodium hydroxide aqueous solution 10 B. 11 B boric acid adsorption, separation efficiency then deteriorates.After the precipitation reaction of ferric chloride-ferrous chloride is carried out by the ammonia-nitrogen-containing gas flow, the process of generating ferroferric oxide nanoparticles is finished, the sulfonic acid group is changed from the trivalent iron type to the ammonium type (i.e., three ion exchange transformation).Adopt high-purity nitrogen to maintain the positive pressure in the drum, the O2 content of the ammonia-nitrogen-containing gas flow is lower than 30ppmv and deoxygenated water, the purpose is to avoid the oxidation of ferrous components, to ensure the generation and surface state of ferroferric oxide nanoparticles.Compared with the resin microspheres of hydrogen type or ammonium type described in step (1), the prepared ferroferric oxide / resin microspheres have significantly improved strength and wear resistance, and are not easy to break in the long-term operation process of the chromatographic column. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is specifically described and illustrated below in conjunction with embodiments.

[0033] Example 1

[0034] In this embodiment, ferroferric oxide / resin microspheres are used to separate boric acid aqueous solution. 10 B. 11 B boron isotope method, using ferroferric oxide / resin microspheres as the stationary phase of the chromatographic column; separation equipment conditions include: the chromatographic column is installed vertically, composed of a transparent organic glass inner tube (inner wall diameter 100mm, clear height 4750mm) and a transparent organic glass outer tube, the outer tube is passed through circulating water for heat preservation or auxiliary temperature control; the ferroferric oxide / resin microspheres are filled with a height of 4590mm (filling volume 36.0L), the bed is covered with a Φ100mm, 60-mesh five-layer stainless steel screen, the screen is filled with Φ3mm porcelain balls with a height of 120mm (the function is to compress the separation bed and disperse the liquid flow), the bed is supported by a Φ100mm, 60-mesh five-layer stainless steel screen and Φ3mm porcelain balls, forming a separation bed; the adsorption liquid (boric acid-monosodium borate aqueous solution) and the desorption liquid (sodium hydroxide aqueous solution) are both in the top-in and bottom-out manner. The upper end of the chromatographic column is provided with a high-purity nitrogen inlet / exhaust interface and a needle valve, and a liquid inlet temperature controller is provided and connected to control the inlet temperature of the adsorbent or desorbent; the liquid inlet temperature controller is connected to the liquid inlet flow pump (plunger pump), and the inlet of the flow pump (adsorbent or desorbent) is selected and controlled by the liquid inlet electric valve. The lower end of the chromatographic column is provided and connected with a liquid outlet temperature detector, a boric acid concentration transmitter (photoelectric), a pH value transmitter, and a liquid outlet electric valve. The liquid inlet electric valve, the liquid inlet flow pump, the liquid inlet temperature controller, the boric acid concentration transmitter, the pH value transmitter, and the liquid outlet electric valve are connected to an intelligent controller, and the intelligent controller is connected to a computer, and the computer settings are used to realize the inlet selection, the flow of the liquid inlet flow pump, the liquid inlet temperature, the cutting and collection of the discharged liquid, and the cutting is performed according to the boric acid concentration and pH value of the discharged liquid.

[0035] After the ferroferric oxide / resin microspheres are loaded into the column, high-purity distilled water at 25°C (made by further distilling deionized pure water after slight boiling to remove impurities such as O2 and CO2) is used to fill the entire chromatographic column. The column is first washed for 10 hours (first, water is introduced at a flow rate of 18 L / h for 1 hour, and then reduced to 9 L / h), and then the column is washed for 10 hours (flow rate 9 L / h) with a sodium hydroxide aqueous solution with a pH value of 10.6 (concentration of 0.0004 mol / L, which is the desorption solution used subsequently); at the same time, circulating water at 25°C is passed from bottom to top in the outer casing.

[0036] Then, the boric acid-monosodium borate aqueous solution was added. 10 B and 11 Dynamic and quasi-dynamic separation test of B.

[0037] The dynamic separation test comprises the following steps:

[0038] (a) First, 4.8 L of 25° C. boric acid-monosodium borate aqueous solution (adsorption solution, 13.3% of the volume of 36.0 L of the ferroferric oxide / resin microsphere bed in the chromatographic column) is introduced, and then a 25° C. sodium hydroxide aqueous solution with a pH value of 10.6 used for washing the column is introduced (desorption solution), and the inlet flow rate is 2.0 L / h (the apparent or axial flow velocity in the separation bed is about 0.51 m / h, and the volume proportion of the resin microspheres in the separation bed is about 50%); the total concentration of boric acid and monosodium borate in the effluent is cut and collected according to the conditions before reaching the maximum value, after reaching the maximum value, 0.5-2 g / L, 2-15 g / L, and ≥15 g / L in terms of boric acid, among which the effluent with a concentration of 2-15 g / L collected after the total concentration in terms of boric acid reaches the maximum value is the enriched effluent. 10 B boric acid aqueous solution; each time the boric acid-monosodium borate aqueous solution is prepared by adding 2 mol / L sodium hydroxide aqueous solution dropwise to 4.4 L saturated boric acid aqueous solution at 25°C under air-tight conditions, adjusting to the desired pH value, then diluting to 4.8 L with water and stirring evenly, wherein the impurity content of the boric acid and sodium hydroxide used in the preparation of the solution is less than 0.03 wt % except for water, and high-purity distilled water is used;

[0039] (b) when the total concentration of boric acid and monosodium borate in the effluent solution increased to 0.5 g / L in terms of boric acid, 4.8 L of a 25° C. boric acid-monosodium borate aqueous solution and a sodium hydroxide aqueous solution with a pH value of 10.6 were again introduced into the chromatographic column;

[0040] (c) repeating steps (a) to (b);

[0041] The column was injected with boric acid-monosodium borate aqueous solution with pH values ​​of 7.0, 7.0, 6.5, 6.5, 6.0, 6.0, 7.0, 7.0, 6.5, 6.5, 6.0, and 6.0 twelve times;

[0042] In the boric acid-monosodium borate aqueous solution, 10 B and 11 The abundance of B was 19.9% ​​and 80.1% respectively, and the total concentration of boric acid and monosodium borate was 0.79 mol / L (49 g / L in terms of boric acid, which is about 90% of the concentration of saturated boric acid aqueous solution). According to the addition amount of 2 mol / L sodium hydroxide aqueous solution, the concentration of monosodium borate was about 0.052 mol / L at pH 7.0, about 0.033 mol / L at pH 6.5, and about 0.015 mol / L at pH 6.0.

[0043] After the dynamic separation test, a quasi-dynamic separation test was performed: the boric acid-monosodium borate aqueous solution at 25°C and pH 6.5 was first introduced for 15 hours (flow rate 2.0 L / h), and then high-purity nitrogen was introduced for 6 hours (99.99v%, flow rate 4.0 L / h, in from top and out from bottom) to discharge most of the solution between the resin microspheres, and then a sodium hydroxide aqueous solution at 25°C and pH 10.6 was introduced for 24 hours (flow rate 2.0 L / h); when the sodium hydroxide aqueous solution at pH 10.6 was first introduced, the liquid outlet electric valve was closed, and when the gas in the chromatographic column was exhausted (filled with liquid), the liquid outlet electric valve was opened and all the discharged liquid was collected to obtain the rich 10 B Boric acid aqueous solution.

[0044] The concentration of boric acid and borate in aqueous solution is determined by chemical method (acid-base titration). 10 B. 11 The abundance of B was determined by ICP-MS.

[0045] The ferroferric oxide / resin microspheres used in Example 1 were obtained by trial production jointly by the applicant and its affiliated units; the preparation method comprises the following steps:

[0046] (1) Take the cross-linking degree of 25 and the specific surface area of ​​152m 2 30 kg of polystyrene-divinylbenzene resin microspheres (white spheres obtained by removing the porogen from a mixed ingredient containing a porogen after being formed into spheres by suspension polymerization, washing with hot water and cold water in succession, and drying, with an outer diameter range of 0.6-0.9 mm and being hydrophobic) with a pore volume of 0.83 mL / g, an average pore diameter of 22 nm, and drying (120°C x 3h drying loss of 0.13 wt%) were placed in a glass-lined reactor (volume 300 L, no water in the reactor, and a discharge port and a liquid discharge port with a polytetrafluoroethylene filter membrane at the bottom of the reactor), the reactor was sealed, evacuated to below 3 kPa (absolute pressure), filled with high-purity nitrogen (99.99v%, O2 content less than 30ppmv) to 30-40 kPa (gauge pressure), and the process was repeated 3 times to replace the air in the reactor and maintain positive pressure in the following operations of this step , press in 135 kg of dimethyl sulfoxide (purity 99.7 wt%), raise the temperature to 60° C. and swell at 60-65° C. for 3 h, start stirring, press in 12 kg of 93 wt% concentrated sulfuric acid for sulfonation treatment, control the temperature at 60-65° C., react for 2.8 h, the sulfonation rate reaches 0.36 mmol / g (i.e., 0.36 meq / g, hydrophilic, the sampling amount is about 35 g based on the total amount of washed and dried sulfonated resin microspheres), stop stirring, discharge the liquid phase through the bottom discharge port of the kettle, inject water to wash until the pH value of the water outlet at the bottom discharge port of the kettle is 2.2, add 5 kg of 3.2 mol / L ammonia solution, stir well, and soak for 4 h, inject water to wash until the conductivity of the water outlet at the bottom discharge port of the kettle is lower than 100 μs / cm, and obtain water-containing ammonium-type macroporous polystyrene-divinylbenzene ion exchange resin microspheres;

[0047] During the sulfonation treatment, the weight ratio of polystyrene-divinylbenzene microspheres, dimethyl sulfoxide, and concentrated sulfuric acid is 1:4.5:0.4;

[0048] (2) The ammonium-type macroporous polystyrene-divinylbenzene ion exchange resin microspheres containing water in step (1) are transferred to a vacuum-evacuable, externally heated, atomizing nozzle-equipped rotary drum (capacity 300 L, with a discharge port and a liquid discharge port with a polytetrafluoroethylene filter membrane; the atomizing nozzle adopts a hydraulic atomization method when spraying liquid and water, and high-purity nitrogen and ammonia-containing nitrogen gas are also introduced by the atomizing nozzle), the rotary drum is sealed and started (rotating), and vacuum dried at 60-70° C. for 8 h to a water content of 0.7 wt %, to obtain dried ammonium-type resin microspheres (about 31.8 kg, 30 g of which was sampled and measured to have a saturated water absorption volume of 0.80 mL / g); the drum is further vacuumed and cooled to 50-60° C., and filled with high-purity nitrogen to a positive pressure, and the atomizing spray concentration is 2. 20.3 L of 4 mol / L ferric chloride-ferrous chloride aqueous solution (the concentrations of ferric chloride and ferrous chloride are 1.6 mol / L and 0.8 mol / L, respectively, and the content of metal impurities is less than 35 mg / L) at a temperature of 50-60° C., spraying time 5 h, the drum continues to rotate for 0.5 h until the surface solution of the resin microspheres is completely absorbed, then stops rotating, stands for 4 h for homogenization (homogenizing the ferric chloride-ferrous chloride aqueous solution initially absorbed in the resin microspheres), and during the spraying and homogenization process, maintain the temperature of the microsphere material at 50-60° C. and the positive pressure in the drum at 30-50 kPa; the spraying volume of the ferric chloride-ferrous chloride aqueous solution is about 80% of the saturated water absorption volume of the dried ammonium type resin microspheres;

[0049] Start the drum, control the external heating temperature at 60-70°C and the required vacuum conditions, and evaporate and remove about 34% of the total weight of water contained in the microsphere material in 10 hours (fix the external heating temperature and adjust the vacuum degree, condense the exhaust steam at 1-3°C through an electronic refrigerator, and control the condensed water amount to be basically uniform and uniform), fill with high-purity nitrogen through the atomizing nozzle to a positive pressure of 30kPa, and reduce the temperature of the microsphere material to 50-60°C; the drum continues to rotate, and introduces a temperature of 50-60°C, a relative humidity of 40-45%, and a content of 50-60°C at a required fixed flow rate. A nitrogen gas stream containing 0.8-1v% ammonia and an O2 content of less than 30ppmv is used to treat the microsphere material. After ventilating for 5.8h, no more ammonia is consumed (i.e., the ammonia content in the outlet and inlet gas streams is the same), and the ammonia-containing nitrogen gas stream is continued for 0.5h. During the treatment with the ammonia-containing nitrogen gas stream, the temperature of the microsphere material is maintained at 50-60°C and the positive pressure in the drum is maintained at 30-50kPa. The ammonia-containing nitrogen gas stream is pressurized by an air pump and then recycled. Its relative humidity is cooled by an electronic refrigerator and condensed to remove part of the water vapor, and then ammonia is added and heated for use.

[0050] The drum continues to rotate and high-purity nitrogen is used to maintain the positive pressure in the drum. 135 kg of deoxygenated water (obtained by removing impurities such as O2 and CO2 from reverse osmosis pure water by micro-boiling) at 40-50 ° C is sprayed on the microsphere material (the amount of water sprayed is about 2.5 times the accumulated volume of the microsphere material). The drum is rotated for 45 minutes to wash the microsphere material once, and the drum is stopped to discharge the liquid between the microspheres; the washing and drainage process is repeated 2-3 times; the drum is stopped to discharge the liquid between the microspheres, and the drum is started to spray the microsphere material with a concentration of 0.8 mol / L, 67.5L of sodium hydroxide aqueous solution at a temperature of 35°C (the spraying amount is about 1.25 times the accumulated volume of the microsphere material), stop the drum, let it stand for 2h and then discharge the liquid between the microspheres; use normal temperature deoxygenated water instead, repeat the water washing and draining process 4 times, the conductivity of the discharged water drops to below 4.6μs / cm, then spray normal temperature deoxygenated water on the microsphere material to immerse the microsphere material, discharge the microsphere material and the immersion water into a container that has been replaced with nitrogen in advance and seal the container to obtain ferrosoferric oxide / resin microspheres.

[0051] The prepared hydrous ferroferric oxide / resin microspheres can be adsorbed by a magnet, have a smooth surface without sediment, and are black in appearance and cross section. Samples taken for testing contain 10.2wt% Fe3O4 on a dry basis, and the net weight after deducting water is estimated to be about 35.1kg. This indicates that the generated ferroferric oxide nanoparticles are loaded in the inner pores of the resin microspheres; in step (2), during the water washing process after the treatment with the ammonia-nitrogen-containing gas flow, when the drum drives the microsphere material to turn over, the surface of the microspheres is fully ground and rinsed, and a small amount of ferroferric oxide nanoparticles deposited on the surface of the microspheres are basically ground and removed.

[0052] The main results of Example 1 are: first, the effluent (rich) collected in the dynamic separation test after the total concentration of boric acid reached the maximum value and the concentration was 2-15g / L 10 B boric acid aqueous solution), detection 10 B abundance is higher than 33.1%; second, the abundance obtained by quasi-dynamic separation experiment 10 B Boric acid aqueous solution, detection 10 B abundance is 24.2%

[0053] Example 2

[0054] After the dynamic and quasi-dynamic separation tests described in Example 1 were completed, the steps (a)-(c) in Example 1 were continued to be operated eighteen times to perform the dynamic separation test of Example 2, with the following differences: A. the column temperature in step (a) was changed to 35°C, and the adsorption liquid, desorption liquid and outer tube circulating water at 35°C were used; B. the adsorption liquid, i.e., boric acid-monosodium borate aqueous solution, was changed from 35°C, saturated boric acid aqueous solution ( 10 B and 11B abundance is 19.9% ​​and 80.1% respectively), add 4.4L of 2mol / L sodium hydroxide aqueous solution, adjust to pH 6.5, dilute to 4.8L with water and stir well to prepare, the total concentration of boric acid and monosodium borate is 1.15mol / L (71g / L in terms of boric acid, about 90% of the concentration of saturated boric acid aqueous solution), and the concentration of monosodium borate is about 0.045mol / L according to the addition amount of 2mol / L sodium hydroxide aqueous solution; C. use desorption solution (sodium hydroxide aqueous solution) with pH values ​​of 10.0, 10.6 and 11.0 respectively, and separate six times each.

[0055] One of the main results of Example 2 is that the effluent collected after the total concentration of boric acid reached the maximum value and the concentration was 2-15 g / L after six separations using the same pH value desorption solution (sodium hydroxide aqueous solution) was sampled and mixed, and the three mixed samples were tested. 10 B abundance is higher than 32.5%.

[0056] Example 3

[0057] After the dynamic separation test described in Example 2 was completed, the steps (a)-(c) in Example 1 were continued for nine times to carry out the dynamic separation test of Example 3, except that: the adsorption liquid, i.e., boric acid-sodium borate aqueous solution, was separated in Examples 1-2 and the 2-15 g / L effluent collected after the total concentration in terms of boric acid reached the maximum value was combined, mixed, evaporated and concentrated, and cooled to a saturated rich solution of 25°C. 10 B Boric acid aqueous solution ( 10 B abundance is 33.0%), add 2mol / L sodium hydroxide aqueous solution, adjust to pH 6.5, dilute to 4.8L with high-purity distilled water and stir well to prepare, the total concentration of boric acid and monosodium borate is 0.80mol / L (49.6g / L in terms of boric acid, about 91% of the concentration of saturated boric acid aqueous solution), according to the addition amount of 2mol / L sodium hydroxide aqueous solution, the concentration of monosodium borate is about 0.034mol / L; the desorption liquid is sodium hydroxide aqueous solution with pH 10.6, and the column temperature is 25℃. The 1-12g / L concentration effluent after the total concentration in terms of boric acid reaches the maximum value is collected separately.

[0058] One of the main results of Example 3 is that the collected effluent with a concentration of 1-12 g / L after the total concentration of boric acid reached the maximum value was sampled and mixed, and then tested. 10 The abundance of B is 50.1%.

[0059] Example 4

[0060] After the dynamic separation test described in Example 3 was completed, the steps (a)-(c) in Example 3 were continued for three times to carry out the dynamic separation test of Example 4, except that: the adsorption liquid, i.e., boric acid-sodium borate aqueous solution, was separated in Example 3, and the 1-12 g / L effluent collected after the total concentration in terms of boric acid reached the maximum value was combined, mixed, evaporated, concentrated, and cooled to a saturated rich solution of 25°C. 10 B Boric acid aqueous solution ( 10 B abundance is 50.4%), add 2mol / L sodium hydroxide aqueous solution, adjust to pH 6.5, dilute to 4.8L with high-purity distilled water and stir well to prepare; the desorption liquid is sodium hydroxide aqueous solution with pH 10.6, and the column temperature is kept at 25°C. The 1-12g / L concentration effluent after the total concentration in terms of boric acid reaches the maximum value is collected separately.

[0061] One of the main results of Example 4 is that the collected effluent with a concentration of 1-12 g / L after the total concentration of boric acid reached the maximum value was sampled and mixed, and then tested. 10 B abundance is higher than 75.3%.

[0062] Example 5

[0063] After the dynamic separation test described in Example 4 is completed, the steps (a)-(c) in Example 3 are continued to be operated once, and the dynamic separation test of this Example 5 is carried out, except that: the adsorption liquid, i.e., boric acid-sodium borate aqueous solution, is separated in Example 4, and the 1-12 g / L effluent collected after the total concentration in terms of boric acid reaches the maximum value is combined, mixed, evaporated and concentrated, and cooled to a saturated rich solution of 25°C. 10 B Boric acid aqueous solution ( 10 B abundance is 75.3%), add 2mol / L sodium hydroxide aqueous solution, adjust to pH 6.5, dilute to 4.8L with high-purity distilled water and stir well to prepare; the desorption liquid is sodium hydroxide aqueous solution with pH 10.6, and the column temperature is kept at 25°C. The 1-12g / L concentration effluent after the total concentration in terms of boric acid reaches the maximum value is collected separately.

[0064] One of the main results of Example 5 is that the collected effluent with a concentration of 1-12 g / L after the total concentration in terms of boric acid reached the maximum value was detected. 10 The abundance of B is 90.8%.

[0065] Example 6

[0066] After the dynamic separation test described in Example 5 was completed, the steps (a)-(c) in Example 1 were continued for three times to carry out the dynamic separation test of Example 6. The pH value of the adsorption liquid, i.e., the boric acid-monosodium borate aqueous solution, was 6.5 each time, and the desorption liquid was still the sodium hydroxide aqueous solution with a pH value of 10.6.

[0067] One of the main results of Example 5 is that the collected effluent with a concentration of 2-15 g / L after the total concentration in terms of boric acid reached the maximum value was detected. 10 B abundance is higher than 32.9%; combined with other results such as the liquid volume of the 2-15g / L concentration discharge liquid, compared with the effect under the same operating conditions in Example 1, it is believed that the separation performance of the separation column after use in Examples 1-6 does not decrease by more than 4%.

[0068] Example 7

[0069] After the dynamic separation test described in Example 6 is completed, the chromatographic column is fed with high-purity distilled water at 25°C for 18 hours (flow rate 2.0 L / h, to wash the column until the boric acid concentration in the effluent is less than 0.1 g / L), and then with a 25°C, 0.4 mol / L sodium hydroxide aqueous solution for 10 hours (flow rate 2.0 L / h), and then with a sodium hydroxide aqueous solution with a pH value of 10.6 for 10 hours (flow rate 2.0 L / h).

[0070] Afterwards, the chromatographic column basically repeated the separation process of Examples 1, 3-5 (one separation operation cycle), and a total of six separation operation cycles were repeated. The desorption solution used a sodium hydroxide aqueous solution with a pH value of 10.6, and the column temperature was 25°C. In each separation operation cycle, the steps (a)-(c) in Example 1 were first operated thirty times, the column temperature was 25°C, the adsorption solution introduced each time had a pH value of 6.5 and a total concentration of 0.79 mol / L (49 g / L in terms of boric acid, which is approximately 90% of the concentration of a saturated boric acid aqueous solution), and the desorption solution continued to use a sodium hydroxide aqueous solution with a pH value of 10.6; the effluent with a concentration of 2-15 g / L collected after the total concentration in terms of boric acid reached the maximum value was combined and mixed, and used as the raw material for repeating the operation of Example 3, and then evaporated and concentrated, and the saturated rich solution was obtained by cooling to 25°C. 10 B boric acid aqueous solution, and used to prepare an adsorption solution with a pH value of 6.5; finally, the separation process and discharge liquid detection of Examples 4-6 were completely repeated. In the process of repeating Examples 1, 3-5, in each example, only the combined mixed solution of the 2-15g / L or 1-12g / L discharge liquid collected after the total concentration in terms of boric acid reached the maximum value was taken for testing once. 10 B abundance.

[0071] The main results of Example 7 include: first, in the discharge liquid after entering the 25°C, 0.4 mol / L sodium hydroxide aqueous solution, the concentration of monosodium borate first increased and then decreased, reaching a maximum of 1.9 g / L in terms of boric acid, indicating that the above-mentioned decrease in the separation performance of the chromatographic column may be related to the deposition of polyboric acid on the surface of the ferroferric oxide nanoparticles loaded in the pores of the resin microspheres. The alkaline washing process can dissolve and depolymerize the deposited polyboric acid to generate sodium borate; second, in the first four separation operation cycles, the separation effects of Examples 1, 3-6 can be reproduced well, and each enrichment 10 Mixture B 10 The concentration, total amount and abundance of B boric acid did not decrease substantially. When the total concentration of boric acid collected in Example 5 reached the maximum value, the effluent with a concentration of 1-12 g / L was detected. 10 B abundance is higher than 90.5%

[0072] Comparative Example 1

[0073] After the dynamic separation test described in Example 7 is completed, the separation process of alkaline washing regeneration and one separation operation cycle described in Example 7 is repeated, with the difference that the desorption liquid (sodium hydroxide aqueous solution with a pH value of 10.6) used in step (a) is replaced by high-purity distilled water.

[0074] The main result of this comparative example 1 is that the separation effects when repeating the processes of Examples 1, 3-5 are slightly lower than those in Example 7. 10 Mixture B 10 The concentration, total amount and abundance of boric acid in Example 7 could not reach the level of the third separation operation cycle as a whole; when the total concentration of boric acid collected in Example 5 reached the maximum value, the effluent with a concentration of 1-12 g / L was detected. 10 The abundance of B is 75.1%.

[0075] Comparative Example 2

[0076] After the dynamic separation test described in Comparative Example 1 is completed, the separation process of alkaline washing regeneration and one separation operation cycle described in Example 7 is repeated, except that the desorption liquid used in step (a) (sodium hydroxide aqueous solution with a pH value of 10.6) is replaced by a dilute hydrochloric acid aqueous solution with a pH value of 4.0 (prepared with high-purity distilled water).

[0077] The main result of this comparative example 2 is that the separation effects when repeating the processes of Examples 1, 3-5 are also slightly lower than those in Example 7. 10 Mixture B 10The concentration, total amount and abundance of boric acid in Example 7 could not reach the level of the third separation operation cycle as a whole; when the total concentration of boric acid collected in Example 5 reached the maximum value, the effluent with a concentration of 1-12 g / L was detected. 10 The abundance of B was 46.3%. In the effluent of alkaline washing regeneration (introducing 25°C, 0.4 mol / L sodium hydroxide aqueous solution), the concentration of monosodium borate first increased and then decreased, reaching a maximum of 1.1 g / L in terms of boric acid.

[0078] The comparison of the effects in Example 7 and Comparative Examples 1-2 shows that, compared with using high-purity distilled water or a dilute hydrochloric acid aqueous solution with a pH value of 4.0 as the desorption liquid, when the present invention uses a sodium hydroxide aqueous solution with a pH value of 10.6 as the desorption liquid, the separation performance and stability of the chromatographic column are higher.

[0079] After the dynamic separation test of Comparative Example 2 was completed, the chromatographic column was rinsed with high-purity distilled water at 25°C for 18h (flow rate 2.0L / h), and then all the separation bed microspheres were unloaded and immersed in high-purity distilled water for storage; the surface of the separation bed layer and the unloaded microspheres were fully inspected before unloading, and no fragmentation of the used ferroferric oxide / resin microspheres was found. The unloaded hydrous ferroferric oxide / resin microspheres can still be adsorbed by a magnet, with a smooth surface and no sediment, and the appearance and cross section are black. The sample was tested to contain 10.1wt% Fe3O4 on a dry basis.

[0080] Example 8

[0081] Using the preparation conditions of the ferroferric oxide / resin microspheres described in Example 1, and basically following the steps (1)-(2) of Example 1, another ferroferric oxide / resin microsphere was prepared with the help of the related units, the main difference being that in step (2), the ferric chloride-ferrous chloride aqueous solution also contained 0.02 mol / L of titanium trichloride. The ferroferric oxide / resin microspheres were subjected to a boric acid aqueous solution in a chromatographic column (filling height 4590 mm, volume 36.0 L) and ancillary equipment conditions identical to those in Example 1. 10 B. 11 B boron isotope separation experiment.

[0082] After the chromatographic column is installed, first fill the entire chromatographic column with high-purity distilled water at 25°C, wash the column for 10 hours (intake water at a flow rate of 18 L / h for 1 hour, then reduce to 9 L / h), and then wash the column with a sodium hydroxide aqueous solution with a pH value of 10.6 (i.e. the desorption liquid used subsequently) for 10 hours (flow rate 9 L / h); at the same time, circulating water at 25°C is passed through the outer casing from bottom to top.

[0083] Then, according to the method of Example 7, the boric acid-monosodium borate aqueous solution was 10 B and 11The dynamic separation test of B was repeated for a total of 20 separation operation cycles, and the desorption liquid was a sodium hydroxide aqueous solution with a pH value of 10.6, and the column temperature was 25°C. In each separation operation cycle, the steps (a)-(c) in Example 1 were first operated 30 times, the column temperature was 25°C, the adsorption liquid introduced each time had a pH value of 6.5 and a total concentration of 0.79 mol / L (49 g / L in terms of boric acid, which is about 90% of the concentration of a saturated boric acid aqueous solution), and the desorption liquid continued to be a sodium hydroxide aqueous solution with a pH value of 10.6; the effluent with a concentration of 2-15 g / L collected after the total concentration in terms of boric acid reached the maximum value was combined and mixed, and used as the raw material for repeating the operation of Example 3, and then evaporated and concentrated, and the saturated rich solution obtained by cooling to 25°C was 10 B boric acid aqueous solution, and used to prepare an adsorption solution with a pH value of 6.5; finally, the separation process and discharge liquid detection of Examples 4-6 were completely repeated. In the process of repeating Examples 1, 3-5, in each example, only the combined mixed solution of the 2-15g / L or 1-12g / L discharge liquid collected after the total concentration in terms of boric acid reached the maximum value was taken for testing once. 10 B abundance.

[0084] The main results of the dynamic separation test include: in the first sixteen separation operation cycles, the separation effects of Examples 1, 3-6 can be basically reproduced, and the enrichment 10 Mixture B 10 The concentration, total amount and abundance of boric acid B were basically the same. When the total concentration of boric acid collected in Example 5 reached the maximum value, the effluent with a concentration of 1-12 g / L was detected. 10 In the last four separation cycles, the abundance of each 10 Mixture B 10 The concentration, total amount and abundance of B boric acid decreased slightly. When the total concentration of boric acid collected in Example 5 reached the maximum value, the effluent with a concentration of 1-12 g / L was detected. 10 The abundance of B showed a decreasing trend and dropped to 90.1% in the twentieth separation operation cycle.

[0085] After the dynamic separation test, the chromatographic column was sequentially fed with high-purity distilled water for 18 h (25° C., flow rate 2.0 L / h, until the boric acid concentration in the effluent was less than 0.1 g / L), 0.4 mol / L sodium hydroxide aqueous solution for 10 h (25° C., flow rate 2.0 L / h), and sodium hydroxide aqueous solution with a pH value of 10.6 for 10 h (25° C., flow rate 2.0 L / h) for regeneration; then, the chromatographic column was subjected to boric acid-monosodium borate aqueous solution according to the above conditions of Example 8. 10 B and 11 The dynamic separation test of B was repeated for a total of 20 separation operation cycles.

[0086] The main results include: First, in the effluent after entering the 25°C, 0.4 mol / L sodium hydroxide aqueous solution, the concentration of monosodium borate also increased first and then decreased, reaching a maximum of 1.2 g / L in terms of boric acid, indicating that the above-mentioned decrease in the separation performance of the chromatographic column is also related to the deposition of polyboric acid on the surface of the ferroferric oxide nanoparticles loaded in the inner pores of the resin microspheres. The alkaline washing process can dissolve and depolymerize the deposited polyboric acid and generate sodium borate; second, the chromatographic column can fully reproduce the separation effect of the previous 20 separation operation cycles in the 20 separation operation cycles after alkaline washing regeneration. This shows that the alkaline washing process has a good regeneration effect on the chromatographic column, and the stability of the separation performance of the chromatographic column is relatively high under the separation operation conditions.

[0087] From the alkali washing regeneration effect in Examples 7 and 8, the number of separations before alkali washing regeneration and the maximum concentration of monosodium borate in the effluent during the alkali washing process calculated as boric acid, it can be seen that in step (2) of the preparation process of ferrosoferric oxide / resin microspheres, adding 0.02 mol / L of titanium trichloride to the ferric chloride-ferrous chloride aqueous solution has a significant effect on improving the separation performance and stability of the chromatographic column.

[0088] Example 9

[0089] Using the preparation conditions of the ferroferric oxide / resin microspheres described in Example 1, the steps (1)-(2) of Example 8 were basically followed to prepare another ferroferric oxide / resin microsphere with the related units, the main difference being that in step (2), 20.3 L of 3.0 mol / L ferric chloride-ferrous chloride aqueous solution (the concentrations of ferric chloride and ferrous chloride were 2.0 mol / L and 1.0 mol / L, respectively) was used instead. The ferroferric oxide / resin microspheres were loaded into the chromatographic column (filling height 4590 mm, volume 36.0 L) after the separation operation in Example 7 was completed, and other conditions remained unchanged, and the boric acid aqueous solution was used. 10 B. 11 Dynamic separation experiment of B boron isotopes.

[0090] The prepared hydrous ferroferric oxide / resin microspheres can be adsorbed by a magnet, have a smooth surface without sediment, and are black in appearance and cross section. Samples taken for detection contain 12.4wt% of Fe3O4 on a dry basis, indicating that the generated ferroferric oxide nanoparticles are loaded in the inner pores of the resin microspheres; in step (2), during the water washing process after the treatment with the ammonia-nitrogen-containing gas flow, when the drum drives the resin microsphere material to turn over, the surface of the resin microspheres is fully ground and rinsed, and a small amount of ferroferric oxide nanoparticles deposited on the surface of the resin microspheres are basically ground and removed.

[0091] The main results of the dynamic separation test include: compared with the corresponding use process in Example 8, the overall separation effect of the chromatographic column is slightly better in the first fourteen separation operation cycles after being put into use, and the collected boric acid concentration of 1-12g / L 10 B Boric acid aqueous solution 10 The abundance of B was more than 92.6% and relatively stable. In the next six separation operation cycles, the separation performance of the chromatographic column decreased slightly, and the collected boric acid concentration of 1-12 g / L was 10 B Boric acid aqueous solution 10 The abundance of B showed a decreasing trend, dropping to 90.2% in the 18th separation operation cycle and to 89.4% in the 20th separation operation cycle. The separation effect of the chromatographic column in the 20 separation operation cycles after alkaline washing and regeneration was basically the same as that in the 20 separation operation cycles before alkaline washing and regeneration.

[0092] Comparative Example 3

[0093] This comparative example 3 is a comparative example for preparing ferroferric oxide / resin microspheres.

[0094] Using the preparation conditions of ferroferric oxide / resin microspheres used in Example 1, all the operations of step (1) and part of the operations of step (2) in Example 1 were carried out, with the main differences being:

[0095] In step (1), the amount of 93wt% concentrated sulfuric acid injected is 30kg, and the temperature is controlled at 80-85°C for sulfonation treatment. After the reaction time of 3.6h, the sulfonation rate reaches 4.15mmol / g; when the primary ion exchange transformation treatment from hydrogen type to ammonium type is carried out, 23kg of 8.8mol / L ammonia solution (temperature controlled below 75°C) is slowly added, stirred and soaked for 4h;

[0096] In step (2), the water-containing ammonium macroporous polystyrene-divinylbenzene ion exchange resin microspheres are dried in a rotary drum at 60-70° C. in vacuum for 11 h to a water content of 0.9 wt %, to obtain 58.0 kg of dried ammonium resin microspheres, and the saturated water absorption volume measured by sampling is 0.23 mL / g; it is believed that the dried ammonium resin microspheres have too small a pore volume and a poor effect of loading ferrosoferric oxide in the inner pores, and are not further prepared and utilized.

[0097] Comparative Example 4

[0098] This comparative example 4 is a comparative example for preparing ferroferric oxide / resin microspheres.

[0099] The ferroferric oxide / resin microspheres of Comparative Example 4 were prepared using the same preparation conditions as in Example 1 and in accordance with steps (1) to (2) of Example 1. The main difference is that in step (2), the steps of soaking in aqueous ammonia solution and then washing with water are omitted, and the hydrogen-type resin microsphere material is directly vacuum dried and all subsequent operations are completed, i.e., the primary ion exchange transformation from the hydrogen type to the ammonium type is not performed.

[0100] As a result, the prepared hydrated ferroferric oxide / resin microspheres can be adsorbed by a magnet, have a smooth surface without sediment, and are black in appearance and cross-section. Samples taken for testing contain 10.0 wt% Fe3O4 on a dry basis, indicating that the generated ferroferric oxide nanoparticles are loaded in the inner pores of the resin microspheres.

[0101] Comparative Example 5

[0102] This comparative example 5 is a comparative example for preparing ferroferric oxide / resin microspheres.

[0103] Using the preparation conditions of the ferroferric oxide / resin microspheres used in Example 1, the ferroferric oxide / resin microspheres of Comparative Example 5 were prepared substantially according to steps (1)-(2) of Example 1, with the main difference being that in step (2), the ammonia content of the ammonia-nitrogen gas flow was increased from 0.8-1v% to 2-2.3v%, and no ammonia was consumed during ventilation for 3h.

[0104] As a result, the prepared hydrated ferroferric oxide / resin microspheres can be adsorbed by a magnet, have a smooth surface without sediment, and are black in appearance and cross-section. Samples taken for testing contain 9.7wt% Fe3O4 on a dry basis, indicating that the generated ferroferric oxide nanoparticles are loaded in the inner pores of the resin microspheres.

[0105] Comparative Example 6

[0106] This comparative example 6 is a comparative example for preparing ferroferric oxide / resin microspheres.

[0107] Using the preparation conditions of the ferroferric oxide / resin microspheres used in Example 1, the ferroferric oxide / resin microspheres of Comparative Example 6 were prepared substantially according to steps (1)-(2) of Example 1, with the main difference being that in step (2), the operation of spraying a 0.8 mol / L sodium hydroxide aqueous solution on the resin microsphere material was omitted, and then water was injected for washing until the conductivity of the discharged water dropped to 4.2 μs / cm, i.e., the fourth ion exchange transformation from ammonium type to sodium type was not performed.

[0108] As a result, the prepared hydrated ferroferric oxide / resin microspheres can be adsorbed by a magnet, have a smooth surface without sediment, and are black in appearance and cross-section. Samples taken for testing contain 10.1 wt% Fe3O4 on a dry basis, indicating that the generated ferroferric oxide nanoparticles are loaded in the inner pores of the resin microspheres.

[0109] Comparative Example 7

[0110] This comparative example 7 is a comparative example for preparing ferroferric oxide / resin microspheres.

[0111] Using some of the preparation conditions of the ferroferric oxide / resin microspheres used in Example 1, the ferroferric oxide / resin microspheres of this comparative example were prepared according to the following steps:

[0112] In another glass-lined reactor (volume 600L, no water in the reactor), add the cross-linking degree 25 and specific surface area 152m 2 / g, pore volume 0.83mL / g, average pore diameter 22nm, dried (120℃x3h drying weight loss 0.13wt%) polystyrene-divinylbenzene resin microspheres (the same as used in Example 1, made from a mixed ingredient containing a porogen, after being spheroidized by suspension polymerization, the porogen is removed and the porogen is washed with hot water and cold water successively, and dried to obtain white balls, with an outer diameter range of 0.6-0.9mm, hydrophobic) 20kg, a closed reaction kettle, evacuated to below 3kPa (absolute pressure), and filled with high-purity nitrogen (99.99v%, O2 content less than 30ppmv) to 30-40kPa (gauge pressure) and repeat 3 times, replace the air in the kettle and maintain positive pressure in the following operations of this step, press in 90kg of dimethyl sulfoxide (purity 99.7wt%), raise the temperature to 60℃ and swell at 60-65℃ for 3h, start stirring, press in 20kg of 93wt% concentrated sulfuric acid, control the temperature at 80-85℃ for sulfonation treatment, and the sulfonation rate reaches 4.18mmol / g ( 4.18meq / g, hydrophilic), stop stirring, discharge the liquid phase through the bottom discharge port of the kettle, inject oxygen-free water to wash until the pH of the water outlet at the bottom discharge port is 2.4, add oxygen-free water to the volume of the feed liquid to about 550L; continue stirring, add 9.0L of 2.4mol / L ferric chloride aqueous solution, add 6.76L of 1.6mol / L ferrous chloride aqueous solution after 4h, raise the temperature of the feed liquid to 55℃ after 1h, control the temperature at 55-60℃ and add 8.8mol / L ammonia aqueous solution (dropping time 2.2h) to The pH value of the feed liquid is 8.1, and a coprecipitation reaction is carried out. After 1 hour, stirring is stopped, and the mixture is allowed to stand and age for 10 hours (the strength of the deposition layer on the surface of the resin microspheres gradually increases). Then, the liquid phase (black slurry, containing ferroferric oxide that has not been deposited on the surface of the resin microspheres and can be adsorbed by a magnet) is discharged through the discharge port at the bottom of the kettle, and oxygen-free water is added to wash until the pH value of the water discharged from the discharge port at the bottom of the kettle reaches 5.2. Oxygen-free water is added to immerse the resin microspheres, and the resin microspheres and the immersion water are discharged into a container that has been replaced with nitrogen in advance and the container is sealed to obtain ferroferric oxide / resin microspheres.

[0113] As a result, the prepared hydrous ferroferric oxide / resin microspheres can be adsorbed by a magnet, and have a slightly rough black deposition layer on the surface. The black surface deposition layer has a certain strength but will deform or even fall off when squeezed, and the cross section is light black. The sample was tested to contain 8.6wt% Fe3O4 on a dry basis. The method of separating boron isotopes using ferroferric oxide / resin microspheres, the content and distribution of ferroferric oxide are basically the same as those of Fe3O4@Resin-1 in the master's thesis "Preparation of ferroferric oxide-loaded resin and study of boron isotope separation performance" (Wang Qingfeng, Tianjin University, May 2021).

[0114] The ferroferric oxide / resin microspheres prepared in the above Examples 1, 8, 9 and Comparative Examples 4-7 were sampled 200-220 mL respectively, and the surface moisture was removed by centrifugation and placed on a 350x250 mm stainless steel plate and spread into a thin layer, and then dried in a vacuum drying oven at 65-70 ° C for 5 h to constant weight. The crystalline phase of iron in each ferroferric oxide / resin microsphere was determined by XRD method. It was found that the crystal phase of iron was Fe3O4, and the average grain size was 3.6 nm, 3.4 nm, 3.9 nm, 4.7 nm, 5.2 nm, 3.7 nm, and 12 nm, respectively.

[0115] The ferroferric oxide / resin microspheres prepared in Comparative Examples 4-7 were subjected to chromatographic treatment in boric acid aqueous solution in the same chromatographic column (filling height 4590 mm, volume 36.0 L) and supporting equipment as in Example 1. 10 B. 11 B boron isotope separation test. After each microsphere is loaded into the column, the entire chromatographic column is first filled with 25°C high-purity distilled water, and the column is washed for 10 hours (water is introduced at a flow rate of 18L / h for 1 hour, and then reduced to 9L / h), and then the column is washed for 10 hours (flow rate 9L / h) with a sodium hydroxide aqueous solution with a pH value of 10.6 (i.e., the desorption liquid used subsequently); at the same time, circulating water at 25°C is passed through the outer sleeve from bottom to top; then, the steps (a)-(c) in Example 1 are performed three times to carry out a dynamic separation test. The pH value of the adsorption liquid, i.e., the boric acid-monosodium borate aqueous solution, is 6.5 each time, and the desorption liquid is still a sodium hydroxide aqueous solution with a pH value of 10.6. The main result is that after the total concentration of boric acid collected reaches the maximum value, the concentration of the effluent is 2-15g / L, and the detection 10 The B abundance is lower than 26.2%, and the separation performance is much lower than that of the ferroferric oxide / resin microspheres prepared and used in Examples 1, 8, and 9.

Claims

1. A method for separating boron isotopes using ferroferric oxide / resin microspheres, using a chromatographic column with ferroferric oxide / resin microspheres as the stationary phase, a boric acid-sodium hydroxide aqueous solution with a pH value of 6-7 as the adsorption liquid, and a sodium hydroxide aqueous solution with a pH value of 10-11 as the desorption liquid to obtain a boron isotope-rich 10 B. Aqueous solution of boric acid; The ferroferric oxide / resin microspheres are prepared by the following steps: (1) Cross-linking degree 15-30, specific surface area 100-180m 2 / g, pore volume 0.6-1.0mL / g, dried (120℃x3h baking loss ≤0.2wt%) polystyrene-divinylbenzene resin microspheres, adding dimethyl sulfoxide in air-tight and anhydrous conditions, heating to 50-65℃ for swelling for more than 3h, adding 93-98wt% concentrated sulfuric acid for sulfonation treatment during stirring, controlling the temperature to 55-65℃, and performing solid-liquid separation after the sulfonation rate reaches 0.3-0.4mmol / g, washing the microspheres with water until the pH value is ≥2, adding 2-5mol / L ammonia solution for immersion for 2-5h for primary ion exchange transformation from hydrogen type to ammonium type, washing with water to obtain water-containing ammonium type macroporous polystyrene-divinylbenzene ion exchange resin microspheres; During the sulfonation treatment, the weight ratio of polystyrene-divinylbenzene microspheres, dimethyl sulfoxide, and concentrated sulfuric acid is 1:(4-5):(0.3-0.5); (2) The ammonium-type macroporous polystyrene-divinylbenzene ion exchange resin microspheres containing water in step (1) are transferred to a rotary drum that can be evacuated, equipped with external heating and an atomizing nozzle, sealed and started to rotate, and vacuum dried at 60-70° C. until the water content is less than 1wt% to obtain dried ammonium-type resin microspheres; further evacuated and cooled to 50-60° C., filled with high-purity nitrogen to positive pressure, and atomized sprayed with a ferric chloride-ferrous chloride aqueous solution with a concentration of 2-3 mol / L and a temperature of 50-60° C. for 4-6 hours, and the drum is continuously rotated for 0.5-1 hour until the resin microspheres After all the surface solution is absorbed, the rotation is stopped, and the mixture is allowed to stand for 3-5 hours for homogenization (homogenization of the ferric chloride-ferrous chloride aqueous solution initially absorbed in the resin microspheres) and secondary ion exchange transformation from ammonium type to iron type, and the temperature of the resin microsphere material is maintained at 50-60° C. and the positive pressure in the drum is maintained during the spraying and homogenization and secondary ion exchange transformation process; the spraying volume of the ferric chloride-ferrous chloride aqueous solution is 70-85% of the saturated water absorption volume of the dried ammonium type resin microspheres; in the ferric chloride-ferrous chloride aqueous solution, the molar ratio of ferric chloride to ferrous chloride is 2:1; The drum is started, and the external heating temperature is controlled to be 60-70° C. and the required vacuum conditions are controlled. Within 8-12 hours, 25-40% of the total weight of the water contained in the resin microsphere material is uniformly evaporated and removed, and high-purity nitrogen is filled to positive pressure, and the temperature of the resin microsphere material is reduced to 50-60° C.; the drum continues to rotate, and a nitrogen gas flow with a temperature of 50-60° C., a relative humidity of 35-45%, and an ammonia content of 0.5-1v% is introduced at a required fixed flow rate to treat the resin microsphere material, so that no ammonia is consumed during ventilation for 4-8 hours (that is, the ammonia content in the outlet and inlet gas flows is the same), and the ammonia-containing nitrogen gas flow is continued for 0.5-1 hour to perform a tertiary ion exchange transformation from trivalent iron type to ammonium type; during the treatment with the ammonia-containing nitrogen gas flow, the temperature of the resin microsphere material is maintained at 50-60° C. and the positive pressure in the drum is maintained; The drum continues to rotate and high-purity nitrogen is passed through to maintain the positive pressure in the drum. Deoxygenated water at 40-50°C is sprayed on the resin microsphere material. The amount of water sprayed is 2-3 times the accumulated volume of the resin microsphere material. The drum is rotated for 30-60 minutes to wash the resin microsphere material once. The drum is stopped to discharge the liquid between the resin microspheres. The washing and drainage process is repeated 2-3 times. The drum is stopped to discharge the liquid between the resin microspheres. The drum is started to spray the resin microsphere material with a concentration of 0.8-1 mol / L and a temperature of 30-40 ℃ sodium hydroxide aqueous solution, the spraying amount is 1-1.5 times of the accumulated volume of the resin microsphere material, the drum is stopped, and the mixture is allowed to stand for 2-3 hours for four ion exchange transformation treatments from ammonium type to sodium type, and then the liquid between the resin microspheres is discharged; room temperature deoxygenated water is used instead, and the water washing and draining process is repeated 3-5 times, and then the resin microsphere material is sprayed with room temperature deoxygenated water to immerse the resin microsphere material, and the resin microsphere and the immersion water are discharged into a container pre-substituted with nitrogen and the container is sealed to obtain ferroferric oxide / resin microspheres.

2. The method for separating boron isotopes using ferroferric oxide / resin microspheres as claimed in claim 1, characterized in that: The separation operation conditions include: the chromatographic column is installed vertically, the height-to-diameter ratio is 10-60, the column temperature is 15-35°C, the adsorption liquid and the desorption liquid are both in the top and out the bottom; the boric acid concentration in the boric acid-sodium hydroxide aqueous solution is 80-95% of the saturated concentration in water under the column temperature condition; the apparent or axial flow rate of the adsorption liquid and the desorption liquid in the stationary phase bed is 0.4-0.6m / h.

3. The method for separating boron isotopes using ferroferric oxide / resin microspheres as claimed in claim 2, characterized in that: Equipment conditions include: the chromatographic column adopts a cylindrical barrel, a separation bed filled with the ferroferric oxide / resin microspheres is arranged inside the barrel, a screen and porcelain balls or metal perforated plates are arranged above the separation bed to compress the separation bed and disperse the liquid flow; a screen and a support are arranged under the separation bed; an insulation layer or a circulating water jacket is arranged outside the barrel; electric valves are appropriately arranged in the inlet and outlet interfaces of the chromatographic column or its connecting pipelines, as well as measurement / control components of temperature measuring instruments, concentration meters and flow meters; the electric valves and the instruments are connected to an intelligent controller, the intelligent controller is connected to a computer, and the control of liquid inlet and liquid outlet, solution segmentation logic and flow control are realized through computer settings, thereby controlling the selection of liquid inlet, the destination of liquid outlet and the segmentation and collection of liquid outlet. The measurement components of the concentration meter include a boric acid concentration transmitter and a pH value transmitter.

4. The method for separating boron isotopes using ferroferric oxide / resin microspheres as claimed in claim 3, characterized in that: The volume of the adsorption liquid fed once is 12-15% of the volume of the separation bed.

5. The method for separating boron isotopes using ferroferric oxide / resin microspheres as claimed in claim 1, characterized in that: The content of impurities other than water in the boric acid and sodium hydroxide used in preparing the adsorption liquid and the desorption liquid is less than 0.1wt%; the water used is high-purity distilled water obtained by further distilling deionized water or reverse osmosis water after slight boiling.

6. The method for separating boron isotopes using ferroferric oxide / resin microspheres as claimed in claim 1, characterized in that: To the rich 10 B Boric acid aqueous solution is iteratively separated to obtain 10 Aqueous solution containing boric acid with a B abundance of 90% or more.

7. The method for separating boron isotopes using ferroferric oxide / resin microspheres as claimed in claim 1, characterized in that: When the adsorption and separation efficiency of the chromatographic column decreases, it is regenerated with a 0.3-0.5 mol / L sodium hydroxide aqueous solution.

8. The method for separating boron isotopes using ferroferric oxide / resin microspheres as claimed in claim 1, characterized in that: In step (1), the polystyrene-divinylbenzene microspheres are white balls obtained by removing the porogen from a mixed ingredient containing a porogen through suspension polymerization, washing with water, and drying, and having an outer diameter of 0.6-0.9 mm.

9. The method for separating boron isotopes using ferroferric oxide / resin microspheres as claimed in claim 1, characterized in that: In step (2), the ferric chloride-ferrous chloride aqueous solution also contains 0.01-0.03 mol / L titanium trichloride.

10. The method for separating boron isotopes using ferroferric oxide / resin microspheres as claimed in claim 1, characterized in that: In step (2), the nitrogen gas flow has a temperature of 50-60°C, a relative humidity of 35-45%, contains 0.5-1v% ammonia, and has an O2 content of less than 30ppmv. The relative humidity is controlled by a condensation method or a desiccant method. The drum is filled with 99.99v% nitrogen and maintained at a positive pressure of 15-30kPa.

Citation Information

Patent Citations

  • Magnetic nanometer material preparation method and method for separating boron isotope by treating magnetic nanometer material as simulative moving bed fixing phase

    CN109464981A

Cited By

  • Separation method of boron isotope

    CN120939751A